Activation of the Erk Pathway Is Required for TGF-β1-Induced EMT In Vitro - Xie, Lu (Neoplasia Press Inc., 2004)
Transforming growth factor-β1 (TGF-β1) can be tumorsuppressive through the activation of the Smadmediated signaling pathway. TGF-β1 can also enhance tumor progression by stimulating epithelial-tomesenchymal transition (EMT) through additional pathways. EMT is characterized by the acquisition of a fibroblast-like cell morphology, dissolution of tight junctions, disruption of adherence junctions, and formation of actin stress fibers. There is evidence linking the activation of mitogen-activated protein kinase pathways to the induction of TGF-β1-mediated EMT. However, the role of Erk in the induction of TGF-β1-mediated EMT remains unclear. TGF-β1 treatment of normal murine mammary gland (NMuMG) epithelial cells resulted in increased gene expression of Ras, Raf, MEK1/2, and Erk1/2, as shown by microarray analysis and real-time polymerase chain reaction. Upon 24 and 48 hours of treatment with TGF-β1, NMuMG and mouse cortical tubule (MCT) epithelial cells underwent EMT as shown by changes in cell morphology, delocalization of zonula occludens-1 and E-cadherin from cell-cell junctions, and formation of actin stress fibers. TGF-β1 treatment also resulted in increased levels of phosphorylated Erk and Erk kinase activity. Treatment with an MEK inhibitor, U0126, inhibited increased Erk phosphorylation and kinase activity, and blocked TGF-β1-induced EMT in both cell lines. These data show that TGF-β1 induces the activation of the Erk signaling pathway, which is required for TGF-β1-mediated EMT in vitro.